Effect of UV Curing Temperature on the Preparation and Properties of PMMA-Diacrylate RM82 Composite Membranes and Test of Water/Methanol Uptake - Afrizal Afrizal; Yusmaniar Yusmaniar; Ramadhani Riparro; Imam Hanafi (Jurnal Kimia Sains dan Aplikasi, 2026)
A composite membrane of Polymethylmethacrylate-reactive mesogen RM82 (PMMA-Diacrylate RM82) was prepared by UV curing at 110, 120, 130, 140, and 150°C. FTIR spectroscopy revealed peaks at 1086 cm−1 and 1147 cm−1, indicating the presence of ester functional groups (C-O). An ether functional group (C-O-C) was observed at 1250 cm−1, while aromatic structures were identified at 1605 cm−1. XRD diffractograms showed high-intensity peaks at 2θ angles of 19.13°, 43.62°, and 72.42°, demonstrating that the membrane retained strong crystalline properties. SEM results showed a regular surface morphology with layered structures, whereas the membrane cured at 120°C exhibited an irregular morphology with coarse fragments. POM textures generally displayed sharp, elongated fibrous patterns. Water uptake was relatively low, with a maximum value of 34.2%, while methanol uptake ranged from 9.28% to 40.5%. The conductivity values of the composite membranes ranged from 3.01 × 10−7 to 4.24 × 10−7 S/cm. Conductivity consistently increased with higher UV curing temperatures and membrane thickness. This trend suggests that UV curing temperature enhances electrical conductivity by altering the molecular structure to create more effective conduction pathways.